Bertahan di Tengah Modernitas: Ketahanan Lembaga Pendidikan Surau Minangkabau (Sejak Masa Kolonial hingga Pasca Kemerdekaan): Bertahan di Tengah Modernitas: Ketahanan Lembaga Pendidikan Surau Minangkabau (Sejak Masa Kolonial hingga Pasca Kemerdekaan) - Fauzan, Ahmad Fauzan Baihaqi; Irmalasari, Fitria; Maulana, Arif; Meilala, Bryna Rizkinta Sembiring (Universitas Nasional, 2024)
ABSTRACT I begin this article with admiration for the success of Surau in Minangkabau in maintaining itself as a traditional educational institution in the era of modernization. Surau as an educational institution in Minangkabau remains an integral part of the collective memory of the Minang people as a whole. This paper wants to see how the tradition of Minangkabau people in maintaining the spirit of Surau since the Colonial period to the Modern era and see the pressure of power on the existence of Surau which gave birth to many National figures and Ulama'. The method in this writing uses a qualitative methodology with a historical approach method by collecting data through literature studies. In the data found, the word surau spreads outside in Indonesia and Malaysia, which in daily life is a small building whose main use is for congregational prayer for the surrounding community. In West Sumatra, Surau not only has an educational and worship function, but also has a cultural function. Surau is thought to have existed before Islam came to West Sumatra. It only functions as an application of their culture. Surau in the customary system of community culture belongs to the people, tribe. Furthermore, after Islam entered, the process of Islamization was carried out in all aspects, including cultural institutions. The same thing also applies to pesantren. Seeing the complexity of the problems of Surau educational institutions must also understand the flow of conflict between the Young and the Old. As seen, the Ulama of the Young as a symbol of Islamic renewal openly criticized the practices of the Ulama of the Old who occupied surau-surau. And this paper tries to explain this traditional educational institution in the era of modernization. Keywords: Surau, Minangkabau Tradition, Traditional Educational Institution